2019
DOI: 10.1101/19010264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Pan-Cancer Landscape of Prognostic Germline Variants in 10,582 Patients

Abstract: While clinical data provides physicians with information about patient prognosis, genomic data can further improve these predictions. We analyzed sequencing data from over 10,000 cancer patients and identified hundreds of prognostic germline variants using multivariate Cox regression models. These variants provide information about patient outcomes beyond clinical information currently in use and may augment clinical decisions based on expected tumor aggressiveness. Molecularly, at least twelve of the germline… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Identifying patients with multiple clinically actionable mutations has important implications for patients and their family members, yet much remains unclear regarding the consequence of carrying more than one pathogenic mutation. Our understanding of how combinations of mutations may interact to alter the ultimate profile of cancers in a patient, or their family, is currently very limited [32][33][34]. Certain combinations of mutations may be detrimental in that they increase overall risk of malignancy while others may reduce overall cancer risk, relative to inheritance of the single gene mutation alone.…”
Section: Multiple Pathogenic Mutationsmentioning
confidence: 99%
“…Identifying patients with multiple clinically actionable mutations has important implications for patients and their family members, yet much remains unclear regarding the consequence of carrying more than one pathogenic mutation. Our understanding of how combinations of mutations may interact to alter the ultimate profile of cancers in a patient, or their family, is currently very limited [32][33][34]. Certain combinations of mutations may be detrimental in that they increase overall risk of malignancy while others may reduce overall cancer risk, relative to inheritance of the single gene mutation alone.…”
Section: Multiple Pathogenic Mutationsmentioning
confidence: 99%
“…The identification of tumor‐type agnostic markers to predict outcome in cancer patients is a challenge. However, pan‐cancer studies have reported germline variants associated with outcome across different tumor types 1,10 . In addition, the identification of biomarkers that can indicate which patients would benefit or not from treatment with bevacizumab regardless of tumor type is even more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Germline variants can significantly improve predictions of the survival of cancer patients compared to clinical variables alone. 1 In addition to their prognostic potential, germline variants are also useful to individualize the selection of the most effective treatment. 2,3 This is clearly demonstrated by the example of deficient mismatch repair of germline DNA, which creates tumors responsive to checkpoint inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Second, partial dependence interpretation is less straightforward than marginal dependence and thus appears less frequently in biological and medical studies. Third, due to the noisy nature of data, medical researchers typically prefer to adopt robust versions of dependence metrics [Chatrath et al, 2020], such as the Spearman correlation coefficient; less is known about statistical methods related to robust partial dependence. Finally, differential analysis based on partial dependence tends to be computationally expensive and unable to tackle the scale of our problem.…”
Section: Introduction 1differential Expression and Co-expression Anal...mentioning
confidence: 99%